Three new phosphates with isolated P2O7 units: noncentrosymmetric Cs2Ba3(P2O7)2 and centrosymmetric Cs2BaP2O7 and LiCsBaP2O7. Issue 9 (2nd February 2016) - Li, Lin; Han, Shujuan; Lei, Bing-Hua; Wang, Ying; Li, Hongyi; Yang, Zhihua; Pan, Shilie
Abstract : Three new phosphates, a noncentrosymmetric (NCS) Cs2 Ba3 (P2 O7 )2 and centrosymmetric (CS) Cs2 BaP2 O7 and LiCsBaP2 O7, have been synthesized from high-temperature solutions for the first time. Abstract : Three new phosphates, a noncentrosymmetric (NCS) Cs2 Ba3 (P2 O7 )2 and centrosymmetric (CS) Cs2 BaP2 O7 and LiCsBaP2 O7, have been synthesized from high-temperature solutions for the first time. Analysis of the structures determined by single-crystal X-ray diffraction showed that although the three compounds contained isolated P2 O7 units, they yielded different three-dimensional (3D) networks: Cs2 Ba3 (P2 O7 )2 crystallized in the NCS Orthorhombic space group P 21 21 21, Cs2 BaP2 O7 in the CS monoclinic space group P 21 / n, and LiCsBaP2 O7, having an identical stoichiometry with Cs2 BaP2 O7, crystallized in monoclinic space group, P 21 / c . Structural comparisons suggested the differences between their 3D frameworks to be due to differences between the sizes and coordination environments of the cations. Characterizations including thermal and optical analyses showed Cs2 Ba3 (P2 O7 )2 and Cs2 BaP2 O7 to melt congruently, and Cs2 Ba3 (P2 O7 )2 to exhibit a wide transparent region with a cut-off edge below 176 nm. The NLO properties and electronic structures of these compounds were investigated using first-principles calcualtions.